1984 - Orwell, George; Orwell, George, 1903-1950. (Harlow : Pearson Education, 2003)
Winston Smith lives in a society where the government controls people every second of the day. He fights this world with love. But it's dangerous: love for another person can punished by death, and Big Brother is always watching. Orwell's classic story shows that there is no freedom unless ideas and beliefs can be questioned. This is as true today as when it was written, more than fifty years ago -- P. 4 of cover
Thoughtcrime -- Big Brother is watching you -- The spies -- The Ministry of Truth -- Ownlife -- Acts against the Party -- A political act -- They can't get inside you -- Our leader, Emmanuel Goldstein -- Doublethink -- Inside Winston Smith's head -- Miniluv -- Two and two make five -- The last man -- Room 101
Keywords: Readers; English novels; Dystopian fiction